Impact of Corporate Governance on Financial Returns of Indian Listed Companies - Dey, Sanjeeb Kumar; Sharma, Debabrata (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- In this paper, we have evaluated the relationship of corporate governance with companies’ financial returns using return on assets (ROA) and return on capital employed (ROCE) as proxies. For this purpose, companies listed in Nifty-50 are considered as a sample. Design/Methodology- The present study is conducted on the NIFTY-50 Index with a final sample of 35 companies after excluding banking companies, financial services companies, and companies that did not have the required data in the sample period. Data has been collected for ten years from 2009-10 to 2018-19, and they are analyzed with the help of software packages such as SPSS and Stata. Findings- The results showed that firms’ financial return measures (ROA and ROCE) were significantly affected by governance measures, board committees, and CEO duality. Board size, board meetings, and board independence did show positive relation, but it was not significant. Our analysis observed that corporate governance significantly affected the financial return of Indian listed companies. Practical Implications- Our research work indicated the importance of corporate governance in generating financial returns for Indian listed companies. CEO duality is found to be increasing the ROCE of listed companies in India, and therefore investors should choose such companies where the CEO plays a dual role in the board. Also, policymakers should take into consideration the dual role of CEOs while making changes in company regulations.